Cellulose-siloxane composite particles, method for producing same, and cosmetic
By coating the cellulose particles with polyorganosilsesquioxane to form composite particles, the problems of pollution and environmental impact of synthetic polymer particles in cosmetics are solved, and the effects of sliding, water repellent and biodegradable are achieved.
Patent Information
- Application Number
- CN202380043676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-30
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-10
AI Technical Summary
The synthetic polymer particles in existing cosmetics are light and difficult to remove, resulting in environmental pollution and adsorbing chemical pollutants, which may have adverse effects on the human body. At the same time, the wet treatment method used in the prior art requires organic solvents to affect the environment.
A composite particle made of cellulose particles coated with polyorganosilsesquioxane was developed. The polyorganosilsesquioxane was adhered to the surface of cellulose particles through hydrolysis and condensation reactions, forming microparticles with excellent biodegradability and touch. .
It realizes slipperiness, soft touch and water repellency in cosmetics, and due to the use of water treatment, the pollution to the environment is reduced and the biodegradable effect is provided.
Smart Images

Figure CN119301180A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to cellulose-silicone composite particles, a method for producing the same, and cosmetics. Background Art
[0002] In the past, various polymer microparticles have been proposed according to their uses. For example, microparticles contained in cosmetics have various purposes. The purpose of containing microparticles in cosmetics is to improve the spreadability of cosmetics, to change the touch, to provide a wrinkle blurring effect, and to improve the slipperiness of foundations, etc.
[0003] In particular, particles with high sphericity have an excellent touch and can achieve a light scattering (soft focus) effect due to their physical properties and shape. When such particles are used in foundation, etc., they can fill in the unevenness of the skin to make it smooth and scatter light in various directions, thereby making wrinkles less noticeable (soft focus).
[0004] In order to achieve the purpose and effect of such cosmetics, the microparticles contained in the cosmetics are required to have a narrow particle size distribution and high sphericity. As such microparticles, microparticles composed of polyamides such as nylon 12, synthetic polymers such as polymethyl methacrylate (PMMA) and polystyrene (PS) have been proposed.
[0005] However, these fine particles made of synthetic polymers have a specific gravity as light as 1 or less and a particle size too small, so they tend to float in water and cannot be removed by wastewater treatment facilities. They sometimes flow directly into rivers or into the sea through rivers. Therefore, there is a problem of contamination of the ocean and the like by these fine particles made of synthetic polymers.
[0006] Furthermore, these fine particles composed of synthetic polymers have the property of adsorbing trace amounts of chemical pollutants in the environment. Therefore, there are concerns that the fine particles adsorbing chemical pollutants may be ingested by plankton and fish, causing various effects such as adverse effects on the human body.
[0007] Due to such concerns, attempts have been made to replace microparticles of synthetic polymers used in various applications with biodegradable particles.
[0008] As a representative biodegradable resin, there is cellulose. Cellulose is excellent in that it can be obtained from natural raw materials such as wood and cotton that do not compete with food and feed. Therefore, the development of microparticles containing cellulose is expected.
[0009] In addition, synthetic resin powders with polysiloxane as the main raw material have been used in many cosmetics such as hair cosmetics, makeup cosmetics, sunscreens, etc. as an important component for forming a uniform film on the surface of skin and hair and providing moisture and smoothness, or imparting water repellency and water resistance. For example, Japanese Patent Publication No. 07-196815 (Patent Document 1) discloses polysiloxane microparticles, which are considered to have a soft touch, no agglomeration, and excellent dispersibility. Therefore, although it is suitable for use as a cosmetic, it is still necessary to develop a more excellent resin powder.
[0010] WO2020 / 188698 discloses that cellulose acetate particles are surface-treated with a lipophilicity-imparting agent containing a polysiloxane component and are formulated into a cosmetic composition. However, as this method, the lipophilicity-imparting agent is attached to the cellulose acetate particles by a wet treatment method, which requires the use of an organic solvent such as n-hexane, and therefore, there is a demand for the development of water-based composite particles that take the environment into consideration.
[0011] Prior art literature
[0012] Patent Literature
[0013] Patent Document 1: Japanese Patent Application Laid-Open No. 07-196815
[0014] Patent document 2: WO2020 / 188698 Summary of the invention
[0015] Problems to be solved by the invention
[0016] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide fine particles having excellent biodegradability and touch by coating biodegradable cellulose particles with polysiloxane which imparts slipperiness, water repellency, etc. to form composite particles.
[0017] Means for solving problems
[0018] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have developed composite particles in which cellulose particles are coated with polyorganosilsesquioxane, thereby completing the present invention.
[0019] That is, the present invention provides composite particles and a method for producing the same, and cosmetics containing the composite particles. The composite particles are composite particles composed of particles of cellulose or a cellulose derivative and polyorganosilsesquioxane attached to the surface of the particles, wherein the polyorganosilsesquioxane is a polymer of an organic trialkoxysilane in an amount of 3 to 80 parts by mass relative to 100 parts by mass of the particles.
[0020] Effects of the Invention
[0021] When the composite particles of the present invention are incorporated into cosmetics and used, the cosmetics can be provided with slipperiness, soft touch, water repellency, etc. Therefore, the composite particles of the present invention can be incorporated into a variety of cosmetics such as hair cosmetics, makeup cosmetics, and sunscreens. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Figure 1 This is an electron micrograph of the surface of the composite particles obtained in Example 4.
[0023] Figure 2 : Figure 2 These are an enlarged electron microscope photograph of the surface of the composite particles obtained in Example 4 (a) and an image obtained by superimposing an elemental mapping image of silicon and an elemental mapping image of carbon (b).
[0024] Figure 3 : Figure 3 This is an electron micrograph of the surface of the composite particles obtained in Comparative Example 5. DETAILED DESCRIPTION
[0025] The present invention provides composite particles comprising particles of cellulose or a cellulose derivative and polyorganosilsesquioxane attached to the surface of the particles, wherein the polyorganosilsesquioxane is a polymer of an organotrialkoxysilane in an amount of 3 to 80 parts by mass, preferably 5 to 70 parts by mass, and more preferably 15 to 55 parts by mass, based on 100 parts by mass of the particles.
[0026] The details are described below.
[0027] (A) Particles of cellulose or cellulose derivatives
[0028] Particles of cellulose or cellulose derivatives (hereinafter collectively referred to as cellulose particles) are particles containing cellulose. Particles of cellulose derivatives such as cellulose acetate and cellulose acetate propionate may also be used. In addition, the shape of cellulose particles is not limited to spherical, but cellulose particles are generally spherical. Spherical cellulose particles are also preferred in the present invention.
[0029] The volume average particle size of the cellulose particles is preferably 1 to 300 μm. Further, it is preferably 1 to 150 μm, and more preferably 1 to 50 μm. More specifically, the volume average particle size is 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, and 45 μm. Here, the volume average particle size of the cellulose particles is a cumulative volume 50% particle size obtained by measuring data using a laser diffraction particle size distribution meter (for example, "SALD2100" manufactured by Shimadzu Corporation).
[0030] Cellulose particles or cellulose derivatives can be produced, for example, by suspending a cellulose acetate solution prepared by dissolving cellulose acetate in an organic solvent in water to prepare a suspension in which cellulose acetate particles are dispersed in water, removing the organic solvent from the suspension, and saponifying the cellulose acetate particles so that the amount of acetic acid relative to the mass of cellulose is 0.5 ppm or less. After the cellulose acetate particles are saponified to obtain cellulose particles, the water can be removed by solid-liquid separation and the cellulose particles can be dried.
[0031] As commercially available cellulose particles, for example, BELLOCIA (registered trademark, manufactured by Daicel, cellulose acetate), Viscopearl (registered trademark, manufactured by RENGO), and ART PEARL NC-400 and NC-800 (manufactured by Negami Industries) can be used.
[0032] (B) Organotrialkoxysilane
[0033] The composite particles of the present invention are obtained by attaching polyorganosilsesquioxane to the surface of the cellulose particles. The polyorganosilsesquioxane is a polymer of an organotrialkoxysilane. The organotrialkoxysilane is represented by the following formula.
[0034] R 1 Si(OR 2 )3
[0035] In the formula, R 1 is an alkyl group having 1 to 30 carbon atoms, R 2 is hydrogen or an alkyl group having 1 to 4 carbon atoms. Methyl is the most preferred. 1 It represents an alkyl group having 1 to 30 carbon atoms, preferably 1 to 12 carbon atoms, and more preferably 1 to 8 carbon atoms. It is most preferably a methyl group. The organotrialkoxysilane may be used alone or in combination of two or more.
[0036] The organotrialkoxysilane is preferably:
[0037] Methyltrimethoxysilane,
[0038] Methyltriethoxysilane,
[0039] Methyltripropoxysilane,
[0040] Ethyltrimethoxysilane,
[0041] Ethyltriethoxysilane,
[0042] Ethyltripropoxysilane,
[0043] Ethyltributoxysilane,
[0044] Propyltrimethoxysilane,
[0045] Propyltriethoxysilane,
[0046] Isobutyltrimethoxysilane,
[0047] Isobutyltriethoxysilane,
[0048] Butyltrimethoxysilane,
[0049] Butyltriethoxysilane,
[0050] Hexyltrimethoxysilane,
[0051] n-Octyltriethoxysilane,
[0052] n-Octyltrimethoxysilane,
[0053] Isooctyltrimethoxysilane,
[0054] Isooctyltriethoxysilane.
[0055] The above-mentioned organotrialkoxysilane is well known and commercially available, for example, as described in U.S. Patent No. 5,300,327 (April 5, 1994), U.S. Patent No. 5,695,551 (December 9, 1997), and U.S. Patent No. 5,919,296 (July 6, 1999).
[0056] As the above-mentioned organotrialkoxysilane, R 1 and R 2 Methyltrimethoxysilane is a methyl group.
[0057] [Manufacturing method]
[0058] The present invention provides a method for producing composite particles, which is a method for producing composite particles composed of (A) cellulose or cellulose derivative particles and polyorganosilsesquioxane attached to the surface of the particles, the method comprising: hydrolyzing and condensing 3 to 80 parts by mass of (B) organotrialkoxysilane relative to 100 parts by mass of the (A) particles in the presence of the (A) particles, water and a base to form polyorganosilsesquioxane, and attaching the polyorganosilsesquioxane to the surface of the (A) particles. The method then includes a step of removing water. Here, the polyorganosilsesquioxane is composed of RSiO 3 / 2 Hereinafter, the production method of the present invention will be described in detail.
[0059] In the production method of the present invention, step (i) is to subject (B) an organotrialkoxysilane to hydrolysis and condensation reaction in the presence of (A) cellulose particles, water and an alkali to form a polyorganosilsesquioxane. The polyorganosilsesquioxane obtained by the hydrolysis and condensation reaction can be obtained in a state of being attached to the cellulose particles.
[0060] The base is used as a catalyst for hydrolysis and condensation reaction of (B) organotrialkoxysilane, or a catalyst for condensation reaction. One base may be used alone, or two or more bases may be used in combination. In addition, the base may be added directly or as an alkaline aqueous solution. Furthermore, the base may be added before adding the organotrialkoxysilane to the aqueous dispersion containing cellulose particles and water, or may be added after the addition of the organotrialkoxysilane.
[0061] The amount of the base added is such that the pH of the aqueous dispersion containing cellulose particles and water is preferably in the range of 9.0 to 13.0, more preferably 9.5 to 12.5. When the pH is in the above range, the hydrolysis and condensation reactions of the organotrialkoxysilane can proceed sufficiently, and the resulting polyorganosilsesquioxane can be sufficiently attached to the surface of the cellulose particles.
[0062] The base is not particularly limited, as long as it is any base that can cause the hydrolysis and condensation reaction of the (B) organotrialkoxysilane to proceed. For example, alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide; alkaline earth metal hydroxides such as calcium hydroxide and barium hydroxide; alkali metal carbonates such as potassium carbonate and sodium carbonate; ammonia; tetraalkylammonium hydroxides such as tetramethylammonium hydroxide and tetraethylammonium hydroxide; or amines such as monomethylamine, dimethylamine, diethylamine, trimethylamine, triethanolamine, and ethylenediamine. Among them, ammonia is the most suitable because it can be easily removed by volatilization from the powder of the obtained cellulose particles. Ammonia can be used in a commercially available ammonia solution.
[0063] The amount of the organotrialkoxysilane (B) added is set to an amount in the range of 3 to 80 parts by mass, preferably 5 to 70 parts by mass, and more preferably 15 to 55 parts by mass, relative to 100 parts by mass of the cellulose particles (A). When the organotrialkoxysilane (B) is less than 1, the effect of siloxane is not exhibited. If it exceeds the upper limit, siloxane that is not coated on the cellulose particles and agglomerated particles are generated. If it exceeds the upper limit, siloxane that is not coated on the cellulose particles and agglomerated particles are generated, the touch becomes worse, and hardness and graininess are also generated when it is formulated as a cosmetic.
[0064] The addition of the (B) organotrialkoxysilane is preferably performed under stirring using a common stirrer such as a propeller blade or a flat blade.
[0065] Furthermore, in order to control the adhesion of the polyorganosilsesquioxane attached to the surface of the cellulose particles, a surfactant or a water-soluble polymer may be added to the aqueous cellulose dispersion.
[0066] The surfactant added to the aqueous dispersion is not particularly limited, and nonionic surfactants, anionic surfactants, cationic surfactants, and amphoteric surfactants may be mentioned. Two or more surfactants may be used as the added surfactant. When the surfactant is added, the amount thereof may be in the range of 0.01 to 10 parts by mass relative to 100 parts by mass of the (A) cellulose particles.
[0067] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyethylene glycol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid esters, polyoxyethylene glycerol fatty acid esters, polyglycerol fatty acid esters, propylene glycol fatty acid esters, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, polyoxyethylene fatty amides, polyoxyethylene modified organopolysiloxanes, and polyoxyethylene polyoxypropylene modified organopolysiloxanes.
[0068] Examples of the anionic surfactant include alkyl sulfate ester salts, polyoxyethylene alkyl ether sulfate ester salts, polyoxyethylene alkylphenyl ether sulfate ester salts, sulfate ester salts of fatty acid alkanolamides, alkylbenzene sulfonates, α-sulfofatty acid ester salts, alkylnaphthalenesulfonic acid, alkyldiphenyl ether disulfosuccinates, fatty acid salts, polyoxyethylene alkyl ether carboxylates, N-acylamino acid salts, monoalkyl phosphate ester salts, dialkyl phosphate ester salts, and polyoxyethylene alkyl ether phosphate ester salts.
[0069] Examples of the cationic surfactant include alkyltrimethylammonium salts, dialkyldimethylammonium salts, polyoxyethylene alkyldimethylammonium salts, dimeroxyethylene alkylmethylammonium salts, trimeroxyethylene alkylammonium salts, alkylbenzyldimethylammonium salts, alkylpyridinium salts, monoalkylamine salts, and monoalkylamideamine salts.
[0070] Examples of the amphoteric surfactant include alkyl dimethylamine oxide, alkyl dimethyl carboxy betaine, alkyl amidopropyl dimethyl carboxy betaine, alkyl hydroxysulfobetaine, and alkyl carboxymethyl hydroxyethyl imidazolinium betaine.
[0071] The water-soluble polymer added to the aqueous dispersion is not particularly limited, and examples thereof include nonionic water-soluble polymers, anionic water-soluble polymers, cationic water-soluble polymers, and amphoteric water-soluble polymers. The water-soluble polymers may be used alone or in combination of two or more. When the water-soluble polymer is added, the amount thereof may be in the range of 0.01 to 10 parts by mass relative to 100 parts by mass of the (A) cellulose particles.
[0072] Examples of the nonionic water-soluble polymer include copolymers of vinyl alcohol and vinyl acetate, polymers of acrylamide, polymers of vinyl pyrrolidone, copolymers of vinyl pyrrolidone and vinyl acetate, polyethylene glycol, polymers of isopropyl acrylamide, polymers of methyl vinyl ether, starch, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, guar gum, xanthan gum, and the like.
[0073] Examples of the anionic water-soluble polymer include polymers of dimethyldiallylammonium chloride, polymers of vinylimidazoline, polymers of methylvinylimidazole chloride, polymers of ethyltrimethylammonium chloride of acrylate, polymers of ethyltrimethylammonium chloride of methacrylate, polymers of acrylamidopropyltrimethylammonium chloride, polymers of methacrylamidopropyltrimethylammonium chloride, epichlorohydrin / dimethylamine polymers, polymers of ethyleneimine, quaternary ammonium compounds of polymers of ethyleneimine, polymers of allylamine hydrochloride, polylysine, cationic starch, cationized cellulose, chitosan, and derivatives thereof obtained by copolymerizing these with monomers having nonionic groups or anionic groups.
[0074] Examples of the amphoteric water-soluble polymer include copolymers of ethyltrimethylammonium chloride of acrylate, acrylic acid and acrylamide, copolymers of ethyltrimethylammonium chloride of methacrylate, acrylic acid and acrylamide, and Hofmann decomposition products of acrylamide polymers.
[0075] One aspect of the manufacturing method of the present invention is to add (B) an organic trialkoxysilane after mixing a base in an aqueous dispersion containing (A) cellulose particles and water. At this time, the organic trialkoxysilane can be added all at once, but it is preferably added slowly over time. The reaction temperature when adding the organic trialkoxysilane is preferably in the range of 0 to 60°C, more preferably 0 to 40°C. If the temperature is within the above range, the polyorganosilsesquioxane can be well attached to the surface of the cellulose particles. Stirring is continued after the addition of the organic trialkoxysilane until the hydrolysis and condensation reactions of the organic trialkoxysilane are completed. In order to complete the hydrolysis and condensation reactions, the reaction can be carried out at room temperature or under heating at about 40 to 100°C, and an additional base can be added as appropriate.
[0076] In another embodiment of the manufacturing method of the present invention, the organic trialkoxysilane can be added before the addition of the base. In this case, the organic trialkoxysilane can be first added to the water. The organic trialkoxysilane can be added to the water at once, but it can also be added slowly over time. In addition, water can be added to the organic trialkoxysilane, or water and the organic trialkoxysilane can be added to the tank at the same time and mixed. The temperature when the organic trialkoxysilane is added to the water is not particularly limited, and can be carried out in a range of 0 to 100° C., for example. Then, the hydrolysis reaction of the organic trialkoxysilane is carried out, and stirring is continued at least until the organic trialkoxysilane is dissolved in the water. At this time, a small amount of acid can be added to promote the hydrolysis reaction.
[0077] Then, an aqueous dispersion containing cellulose particles is added to the solution obtained above, followed by the addition of an alkali. When an alkali is added, a condensation reaction of the hydrolyzate of the organotrialkoxysilane is carried out to generate polyorganosilsesquioxane. However, in this case, it is necessary to stop stirring or stir very slowly before the polyorganosilsesquioxane is generated. If the reaction solution flows at a high speed when the polyorganosilsesquioxane is generated, the polyorganosilsesquioxane cannot be well attached to the cellulose particles.
[0078] The temperature during the condensation reaction is preferably in the range of 0 to 60° C., more preferably in the range of 0 to 40° C. If the temperature is within the above range, the polyorganosilsesquioxane can be well attached to the cellulose particles. The reaction solution can be allowed to stand or be stirred very slowly until the polyorganosilsesquioxane is generated (the polyorganosilsesquioxane is attached to the surface of the cellulose particles). It should be noted that the standing time is preferably in the range of 10 minutes to 24 hours. Then, in order to complete the condensation reaction, a base can be further added, or heating can be performed at 40 to 100° C. In addition, normal stirring can also be further performed.
[0079] In step (ii) of the production method of the present invention, after the polyorganosilsesquioxane is attached to the surface of the cellulose particles, water is removed by volatilization.
[0080] The volatilization and removal of water can be carried out by heating under normal pressure or reduced pressure. For example, a method of removing water by leaving the dispersion liquid to stand under heating can be cited. It should be noted that as a pretreatment for this operation, the dispersion liquid can be concentrated by methods such as filtration separation, centrifugal separation, decantation, etc., and the dispersion liquid can also be washed with water, water-soluble alcohol, etc. as needed.
[0081] When the powder of the composite particles obtained by removing the water by volatilization is agglomerated, it can be crushed by a pulverizer such as a jet mill, a ball mill, or a hammer mill.
[0082] In the composite particles obtained by the above method, the cellulose particles are coated with polyorganosilsesquioxane. Coating with polyorganosilsesquioxane can be confirmed by infrared absorption spectrum. In addition, the coating state can be confirmed by observing the surface by electron microscope photographs. It is particularly preferred that more than 30% of the surface area of the cellulose particles, preferably 30% to 95%, more preferably 40 to 90%, and further preferably 40 to 80% are coated with polyorganosilsesquioxane. When the surface coverage of the cellulose particles is less than 30%, the effect of siloxane is not manifested. When the coverage is large, siloxane and agglomerated particles that are not coated on the cellulose particles are produced, and sometimes the touch becomes worse, and the biodegradability effect of the cellulose particles cannot be expected. The volume average particle size of the composite particles is preferably 1 to 300 μm. Furthermore, it is preferably 1 to 150 μm, and more preferably 1 to 50 μm.
[0083] The static / dynamic friction coefficient of the composite composed of the composite particles is preferably 0.4 or less, and it can be said that the smoothness and slidability are good. When used as a cosmetic described later, the same effect can be provided to the cosmetic. It should be noted that the "complex composed of composite particles" refers to those formed by evenly applying and spreading the composite particles on a substrate such as a biological skin plate.
[0084] The composite particles of the present invention can be used in combination with cosmetics, and the amount of the composite particles relative to the total amount of the cosmetics is 1 to 50% by mass, preferably 1 to 30% by mass. If it is less than the above lower limit, sometimes a sufficient effect cannot be obtained. If it exceeds the above upper limit, there is an unpreferable situation such as obvious whiteness.
[0085] Examples of cosmetic ingredients other than the composite particles of the present invention include oils, solvents, and powders other than the silicone copolymer resin powder.
[0086] Examples of the oil include hydrocarbons, silicone oils, triglycerides, ester oils, fats and oils, waxes, higher fatty acids having 12 to 20 carbon atoms, higher alcohols having 8 to 20 carbon atoms, and the like. Low-boiling silicone oils, low-boiling isoparaffin hydrocarbons, triglycerides, and ester oils are particularly preferred. For example, examples of low-boiling silicone oils include octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and tetradecamethylcyclohexasiloxane. Examples of ester oils include fatty acid esters having 6 to 20 carbon atoms or glycerol fatty acid esters.
[0087] The content of the oil in the cosmetic varies depending on the dosage form of the cosmetic, and any amount may be within a range that does not impair the effects of the present invention. Preferably, the content is 0.1 to 95% by mass, more preferably 1 to 80% by mass, relative to the total of the powder and the resin powder component of the present invention. When the content is less than the above lower limit, the effects of the oil such as slipperiness and moisturizing properties may not be exerted. When the above upper limit is exceeded, there is a tendency for storage stability to decrease.
[0088] Examples of the solvent include middle and lower alcohols, aromatic alcohols, and the like, but preferably are lower alcohols having 1 to 4 carbon atoms such as isopropyl alcohol. The content of the solvent in the cosmetic of the present invention varies depending on the dosage form of the cosmetic, but may be an amount that does not impair the effects of the present invention, and may preferably be 0.1 to 80% by mass, more preferably 1 to 50% by mass, relative to the total of the powder and the resin powder component of the present invention.
[0089] Powder refers to materials that are generally used in (make-up) cosmetics, and is not particularly limited. Usually, the average particle size is 0.1 to 50 μm, and examples include inorganic coloring pigments, inorganic white pigments, coloring materials such as organic pigments, pearlescent agents, extender pigments, organic powders, and the like.
[0090] Examples of the powder include titanium oxide, zirconium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, talc, mica, kaolin, sericite, muscovite, synthetic mica, phlogopite, lepidolite, biotite, lepidolite, silicic acid, anhydrous silicic acid, aluminum silicate, sodium silicate, sodium magnesium silicate, magnesium silicate, magnesium aluminum silicate, calcium silicate, barium silicate, strontium silicate, metal tungstate, hydroxyapatite, vermiculite, aluminum hydroxide (HIGILITE), bentonite, montmorillonite, hectorite, zeolite, ceramic powder, calcium hydrogen phosphate, aluminum oxide, aluminum hydroxide, boron nitride, boron nitride, and the like; examples of the organic powder include polyamide powder, polyester powder, polyethylene powder, polypropylene powder, and polystyrene powder. powder, polyurethane powder, benzoguanamine powder, polymethylbenzoguanamine powder, polytetrafluoroethylene powder, polymethyl methacrylate powder, cellulose, silk powder, nylon powder, 1,2-nylon, 6-nylon, polysiloxane powder, polymethylsilsesquioxane spherical powder, styrene-acrylic acid copolymer, divinylbenzene-styrene copolymer, vinyl resin, urea resin, phenolic resin, fluororesin, silicone resin, acrylic resin, melamine resin, epoxy resin, polycarbonate resin, microcrystalline cellulose powder, starch powder, lauroyl lysine, etc.; as the surfactant metal salt powder, zinc stearate, aluminum stearate, calcium stearate, magnesium stearate, zinc myristate, magnesium myristate, zinc palmitate, zinc laurate, cetyl phosphate zinc, calcium cetyl phosphate, sodium zinc cetyl phosphate, etc.; as the color pigment, there can be mentioned inorganic red pigments such as red iron oxide, iron oxide, iron hydroxide, and iron titanate, inorganic brown pigments such as γ-iron oxide, inorganic yellow pigments such as yellow iron oxide and loess, inorganic black pigments such as black iron oxide and carbon black, inorganic purple pigments such as manganese violet and cobalt violet, inorganic green pigments such as chromium hydroxide, chromium oxide, cobalt oxide, and cobalt titanate, inorganic blue pigments such as Prussian blue and ultramarine, Red No. 3, Red No. 104, Red No. 106, Red No. 201, Red No. 202, Red No. 204, Red No. 205, Red No. 220, Red No. 226, Red No. 227, Red No. 228, Red No. 230, Red No. 401, Red No. 50 5, Yellow 4, Yellow 5, Yellow 202, Yellow 203, Yellow 204, Yellow 401, Blue 1, Blue 2, Blue 201, Blue 404, Green 3, Green 201, Green 204, Green 205, Orange 201, Orange 203, Orange 204, Orange 206, Orange 207 and other tar pigments, carminic acid, lac acid, safflower glycoside, brazilwood, crocin and other natural pigments, etc.; as pearlescent pigments, titanium oxide coated mica, mica titanium, iron oxide treated mica titanium, bismuth oxychloride, titanium oxide coated bismuth oxychloride, titanium oxide coated talc, fish scale foil, titanium oxide coated colored mica, etc. can be mentioned;Examples of metal powder pigments include aluminum, gold, silver, copper, platinum, stainless steel and other metal powders. ;
[0091] Furthermore, in addition to the above-mentioned constituent components, the cosmetics of the present invention may also contain other ingredients commonly found in cosmetics, such as surfactants, oily components, polymer compounds, gelling agents, alkali agents, polyols, pH adjusters, ultraviolet absorbers, antioxidants, preservatives, anti-inflammatory agents, skin beautifying ingredients, and fragrances, in accordance with the purpose, within the range of quantity and quality that do not impair the effects of the composite particles of the present invention.
[0092] As cosmetics of the present invention, for example, makeup cosmetics such as foundation, white powder, eye shadow, eyeliner, eyebrow pencil, blush, lipstick, nail color, emulsion, cream, lotion, calamine lotion, sunscreen, tanning agent, aftershave cream, pre-shave lotion, mask material, anti-acne cosmetics, basic cosmetics such as essence, shampoo, conditioner, hair dye, hair growth agent, setting agent, hair care agent, perm agent and other hair cosmetics, talcum powder, deodorant, depilatory, soap, shower gel, bath agent, hand soap, perfume, etc. The polysiloxane copolymer resin powder of the present invention is preferably used for powder cosmetics such as foundation, white powder, eye shadow, eyebrow pencil, etc.
[0093] Example
[0094] The present invention is described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples. It should be noted that in the following Examples, parts and % represent parts by mass and % by mass, respectively.
[0095] [Example 1]
[0096] 100 parts by mass of spherical cellulose particles (A-1) with an average particle size of 7 μm, 830 parts by mass of ion exchange water, and 1.6 parts by mass of dodecyltrimethylammonium chloride (cationic BB, cationic emulsifier manufactured by NOF Corporation) were placed in a 500 ml reactor and stirred for 30 minutes. 22 parts by mass of 25% ammonia water were added to control the pH to 11-12 (table pH meter HM-42X (manufactured by DKK Toa Co., Ltd.) and after cooling to 5°C, 22.5 parts by mass of methyltrimethoxysilane (KBM13, manufactured by Shin-Etsu Chemical Co., Ltd.) were added over 20 minutes. After aging at 8°C for 1 hour, the temperature was raised to 55°C, 53 parts by mass of 25% ammonia water were added, and aging was performed for 1 hour to obtain a slurry. The slurry was filtered by suction to separate the solid and liquid, and allowed to stand and dry, resulting in a monodisperse and water-repellent powder. By electron microscopy, it was confirmed that the composite particles were polymethylsilsesquioxane attached to the surface of the granular cellulose particles.
[0097] [Example 2]
[0098] The procedure of Example 1 was repeated except that methyltrimethoxysilane was changed to 15 parts by mass to obtain a monodisperse water-repellent powder. The electron microscope confirmed that the powder was a composite particle in which polymethylsilsesquioxane was attached to the surface of the particulate cellulose particles.
[0099] [Example 3]
[0100] The procedure of Example 1 was repeated except that methyltrimethoxysilane was changed to 55 parts by mass to obtain a monodisperse water-repellent powder. Using an electron microscope, it was confirmed that the powder was a composite particle in which polymethylsilsesquioxane was attached to the surface of the particulate cellulose particles.
[0101] [Example 4]
[0102] The procedure of Example 1 was repeated except that the spherical cellulose particles having an average particle size of 7 μm were replaced with spherical cellulose particles having an average particle size of 15 μm (A-2) and the amount of methyltrimethoxysilane was changed to 40 parts by mass, thereby obtaining a monodisperse water-repellent powder.
[0103] The composite particles were observed using an electron microscope, and it was confirmed that there were particles with a particle size of about 100 nm on the particle surface. In addition, the infrared absorption spectrum was measured using a potassium bromide tablet method using an FT-IR measuring device (manufactured by Shimadzu Corporation). The results showed that at a wave number of 2960 cm -1 、1260cm -1 , and 1100~1020cm -1 Characteristic absorption was confirmed at the surface of the granular cellulose particles. This confirmed that the particles were composite particles in which polymethylsilsesquioxane was attached to the surface of the granular cellulose particles. An electron micrograph of the surface of the composite particles is shown in FIG. Figure 1 In addition, an electron microscope photograph (a) obtained by observing the surface of the composite particles and a corresponding image (b) obtained by superimposing an elemental mapping image of silicon and an elemental mapping image of carbon obtained by SwiftED3000 (manufactured by HITACHI) are shown in FIG. Figure 2 .
[0104] [Example 5]
[0105] Composite particles were obtained by repeating the procedure of Example 1 except that the spherical cellulose particles having an average particle size of 7 μm were replaced with spherical cellulose particles having an average particle size of 15 μm (A-2) and the amount of methyltrimethoxysilane was changed to 15 parts by mass.
[0106] [Example 6]
[0107] Composite particles were obtained by repeating the procedure of Example 1 except that the cellulose particles of Example 1 were replaced with spherical cellulose particles (A-3) having an average particle size of 5 μm.
[0108] [Comparative Examples 1 to 3]
[0109] The cellulose particles (A-1), (A-2), and (A-3) were evaluated without being treated with methyltrimethoxysilane.
[0110] In Comparative Example 4, a silane resin powder (average particle size 5 μm, X-52-1621, manufactured by Shin-Etsu Chemical Co., Ltd., B-2) was evaluated.
[0111] [Comparative Example 5]
[0112] The procedure of Example 1 was repeated except that the amount of methyltrimethoxysilane was changed to the amount shown in Table 2 to obtain composite particles. The surface image of the particles of Comparative Example 5 is shown in FIG. Figure 3 .
[0113] The composite particles obtained above were evaluated as follows.
[0114] 〈Cover rate〉
[0115] The average coverage was calculated visually from electron micrographs of the surfaces of ten composite particles.
[0116] The calculation is performed in the following format.
[0117] Coverage rate = Coverage area / Surface area × 100
[0118] <Methods for measuring touch and spreadability>
[0119] An appropriate amount of the powder sample was placed on a finger, brought into contact with black carbon paper, and slid across the paper surface in one go. The feeling of sliding was defined as touch, and the length of the sliding track was defined as spreadability, which was evaluated at the following three levels.
[0120] ○: Has a unique and good sliding feel
[0121] △: Slightly good sliding feeling
[0122] ×: The finger feels resistance but no sliding sensation
[0123] <Method for measuring friction coefficient>
[0124] About 1 g of the powder sample was evenly spread on a biological skin plate (Beaulax) to prepare a sample sheet having a composite body composed of composite particles. Using HEIDON TYPE-38 (Shinto Science Co., Ltd.), a pressure head with a weight of 100 g was brought into vertical contact with the composite body of the sample sheet, and the friction force when moving at 3 cm / min was measured, and the friction coefficient was calculated from the friction force. The pressure head used had a contact surface of 12 mm in diameter and an artificial leather pressing sheet was installed on the contact surface with the composite body.
[0125] The preferred range of the static and dynamic friction coefficient of the composite composed of composite particles is 0.4 or less, and the static and dynamic friction coefficients are both 0.01 to 0.40. The smaller the static and dynamic friction coefficients, the better the sliding property. In particular, when it is 0.4 or less, the smoothness and easy sliding property are good, so it is preferred.
[0126] The static friction coefficient is an indicator of the force required to start a movement from a stationary state. If it is large, it is easy to feel stuck and uncomfortable.
[0127] <Contact angle>
[0128] The contact angle was measured as follows.
[0129] A sample piece similar to the above friction coefficient measurement was prepared, and a 10 μm water droplet was dropped thereon, and the contact angle value was measured 0.3 seconds later using a contact angle meter CA-D manufactured by Kyowa Interface Science Co., Ltd. The preferred range of the water repellent agent is a contact angle of 110° or more.
[0130] <Light diffusion intensity (light diffusion evaluation)>
[0131] Powder sample 5g is dropped into clear lacquer 45g, dispersed in 2 minutes with dispersing mixer 3000rpm.Dispersion liquid is dripped on black carbon paper in the mode of becoming diameter 2cm circle, and is coated with 5MIL applicator and filmization.After air-drying, 3 different points on the film are measured with gloss meter, and average value is adopted.85 ° of reflected light intensity is smaller, then becomes matte processing more, and it can be said that light diffusion is good.
[0132] [Table 1]
[0133]
[0134] [Table 2]
[0135]
[0136] A-1: Cellulose particles with an average particle size of 7 μm
[0137] A-2: Cellulose particles with an average particle size of 15 μm
[0138] A-3: Cellulose particles with an average particle size of 5 μm
[0139] B-1: Methyltrimethoxysilane (KBM13, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0140] B-2: Silane resin powder (average particle size 5 μm, X-52-1621, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0141] [Example 7]
[0142] Using the composite particles produced in Example 1, a foundation was prepared in the following blending manner.
[0143] Foundation
[0144] Ingredients (%)
[0145] (1) Cellulose-silicone composite particles 3.0 of Example 1
[0146] (2) Acrylic polysiloxane treated talc (Note 1) Balance
[0147] (3) Acrylic polysiloxane treated sericite 10.0
[0148] (4) Metal soap treated mica 2.0
[0149] (5)Synthetic Phlogopite 5.0
[0150] (6) Silicon dioxide spherical powder 5.0
[0151] (7) Polysiloxane-treated titanium dioxide microparticles 12.5
[0152] (8) Silicone treated iron oxide red 0.6
[0153] (9) Polysiloxane treated yellow iron oxide 2.0
[0154] (10) Polysiloxane treated black iron oxide 0.2
[0155] (11) Polysiloxane treated titanium oxide 6.0
[0156] (12) Diisostearyl Malate 2.0
[0157] (13) Glyceryl triisostearate 0.4
[0158] (14) Methyl polysiloxane 3.5
[0159] (15) Ultraviolet absorber 5.0
[0160] (16) Appropriate amount of preservatives
[0161] (17) Spices to taste
[0162] (Note 1) NS talc JA-46R-3F (produced by Kakuhachirin Foil Co., Ltd.)
[0163] [Examples 8 to 12, Comparative Examples 6 to 10]
[0164] A foundation was prepared in the same formulation as in Example 7 except that the powder was replaced with the composite particles obtained in Examples 2 to 6 and Comparative Examples 1 to 5.
[0165] [Example 13]
[0166] A foundation was prepared in the same formulation as in Example 7 except that the amount of the composite particles used in Example 7 was changed to 20%.
[0167] The powder foundation obtained above was subjected to the following evaluation. The results are shown in Tables 3 and 4.
[0168] [Touch, Sliding Properties]
[0169] A use test was conducted by 20 professional judges, and evaluation was performed on each evaluation item related to the feel and slip of the cosmetics based on the following scoring criteria. Then, the scores given by each judge were totaled, and evaluation was performed based on the following evaluation criteria.
[0170] (Rating basis)
[0171] 5 points: Excellent
[0172] 4 points: Excellent
[0173] 3 points: Average
[0174] 2 points: Poor
[0175] 1 point: Very poor
[0176] (Evaluation Criteria)
[0177] ◎: Total score is 80 points or above
[0178] ○: Total score is 60 points or more and less than 80 points
[0179] △: Total score is 40 points or more and less than 60 points
[0180] ×: Total score is less than 40 points
[0181] [Table 3]
[0182]
[0183] [Table 4]
[0184]
[0185] As shown in Table 4 above, the foundation using the cellulose particles or silane resin powder without surface treatment has poor touch and slip. For composite particles in which the amount of methyltrimethoxysilane is too small relative to the cellulose particles, the resulting foundation has poor touch and slip. In addition, for composite particles in which the amount of methyltrimethoxysilane is too large relative to the cellulose particles, there is a tendency for the resulting foundation to have poor slip. In contrast, as shown in Table 3 above, the cellulose-siloxane composite particles of the present invention can provide a foundation with excellent touch and slip compared to the cellulose particles without surface treatment.
[0186] When the composite particles of the present invention are formulated and used in cosmetics, the cosmetics can be provided with slipperiness, soft touch, water repellency, etc., and can be formulated in a variety of cosmetics such as hair cosmetics, makeup cosmetics, and sunscreens. In addition, the composite powder of the present invention and the cosmetics containing the composite powder can be expected to have a biodegradable effect.
Claims
1. A composite particle comprising particles of cellulose or a cellulose derivative and polyorganosilsesquioxane attached to the surface of the particles, wherein the polyorganosilsesquioxane is a polymer of an organotrialkoxysilane in an amount of 3 to 80 parts by mass based on 100 parts by mass of the particles.
2. The composite particle according to claim 1, characterized in that The particles of cellulose or cellulose derivatives have a volume average particle size of 1 to 300 μm.
3. The composite particle according to claim 1 or 2, wherein The organic trialkoxysilane is methyltrimethoxysilane.
4. A composite particle comprising particles of cellulose or a cellulose derivative and a polyorganosequioxane attached to the surface of the particle, wherein: At least 30% of the surface area of the particles is covered with the polyorganosilsesquioxane.
5. The composite particle according to claim 4, wherein The particles of cellulose or cellulose derivatives have a volume average particle size of 1 to 300 μm.
6. The composite particle according to claim 4 or 5, wherein The polyorganosilsesquioxane is a polymer of organotrialkoxysilane.
7. The composite particle according to claim 6, wherein The organic trialkoxysilane is methyltrimethoxysilane.
8. A method for producing composite particles comprising (A) particles of cellulose or a cellulose derivative, and polyorganosilsesquioxane attached to the surface of the particles, the method comprising: A step of subjecting 3 to 80 parts by mass of (B) organotrialkoxysilane to hydrolysis and condensation reaction in the presence of the (A) particles, water and a base to form polyorganosilsesquioxane, and attaching the polyorganosilsesquioxane to the surfaces of the (A) particles.
9. The production method according to claim 8, further comprising a step of removing water after the step. 10 . A cosmetic comprising the composite particles according to claim 1 . 11 . The cosmetic according to claim 10 , comprising 1 to 50% by mass of the composite particles based on the total amount of the cosmetic.
12. The composite particle according to any one of claims 1 to 7, wherein The static friction coefficient of the composite body including the composite particles is 0.4 or less.
Citation Information
Patent Citations
Fine silicone particle and its production
JP1995196815A
Water repellent organosilicon compositions
US5300327A
Water repellent composition
US5695551A
Storage-stable water-repellent composition for masonry materials
US5919296A
Cellulose acetate-containing particles, cosmetic composition, and method for producing cellulose acetate-containing particles
WO2020188698A1